Présence du traducteur dans le processus de traduction spécialisée - Tomaszkiewicz, Teresa (Studia Romanica Posnaniensia, 2016)
This article deals with the issue of the role of a translator in translating specialized texts. It is theoretically assumed that a translator of that kind of texts is merely a transferor of information and should not intervene with the meaning of the given text. Numerous studies show, however, that a translator of specialized texts – subject to the nature of the given text – must employ a whole range of translation techniques which aim at explicating certain concealed or unknown messages being conveyed to the receiving party. In this article we strive to prove that these explanatory techniques can take on a totally different dimension when applied to scientific or pragmatic texts. Therefore it can be inferred that translating scientific texts provides for different interventions on the part of the translator than in the case of translating utilitarian texts. Nevertheless, each such intervention is to some extent creative from the point of view of the role of the translator in the process of the transfer.